The six disciplines of breakthrough learning : - Pollock, Roy V. H. (Wiley, 2015)
The book includes: A complete review of research drawn from thousands of insights, goals, and lessons learned Specific strategies and actions that can be put into effect quickly for immediate results A focus on ROI for business leaders wanting to make a clearer connection between dollars spent and new skills gained Checklists in each chapter to help learning organizations perform quality audits of new and existing learning programs The third edition of The Six Disciplines of Breakthrough Learning contains so many new resources and so much thoroughly-revised content that even those who own previous editions will find its reinvigorated approach highly beneficial. Strengthen the link between your learning efforts and your business goals with this increasingly popular, globally recognized resource